Functional Analyses of Flavonol Synthase Genes From Camellia sinensis Reveal Their Roles in Anther Development - Shi, Yufeng; Jiang, Xiaolan; Chen, Linbo; Li, Wei-Wei; Lai, Sanyan; Fu, Zhouping; Liu, Yajun; Qian, Yumei; Gao, Liping; Xia, Tao (Frontiers in Plant Science, 2021)
Flavonoids, including flavonol derivatives, are the main astringent compounds of tea and are beneficial to human health. Many researches have been conducted to comprehensively identify and characterize the phenolic compounds in the tea plant. However, the biological function of tea flavonoids is not yet understood, especially those accumulated in floral organs. In this study, the metabolic characteristics of phenolic compounds in different developmental stages of flower buds and various parts of the tea flower were investigated by using metabolomic and transcriptomic analyses. Targeted metabolomic analysis revealed varying accumulation patterns of different phenolic polyphenol compounds during flowering; moreover, the content of flavonol compounds gradually increased as the flowers opened. Petals and stamens were the main sites of flavone and flavonol accumulation. Compared with those of fertile flowers, the content of certain flavonols, such as kaempferol derivatives, in anthers of hybrid sterile flowers was significantly low. Transcriptomic analysis revealed different expression patterns of genes in the same gene family in tea flowers. The CsFLSb gene was significantly increased during flowering and was highly expressed in anthers. Compared with fertile flowers, CsFLSb was significantly downregulated in sterile flowers. Further functional verification of the three CsFLS genes indicated that CsFLSb caused an increase in flavonol content in transgenic tobacco flowers and that CsFLSa acted in leaves. Taken together, this study highlighted the metabolic properties of phenolic compounds in tea flowers and determined how the three CsFLS genes have different functions in the vegetative and reproductive organs of tea plants. Furthermore, CsFLSb could regulated flavonol biosynthesis in tea flowers, thus influencing fertility. This research is of great significance for balancing the reproductive growth and vegetative growth of tea plants.